Documenting the Results of Audit of the Information Disclosed in the Notes to the Financial Reporting Compiled by International Standards - О. Е. Lubenchenko (Статистика України, 2020)
Financial reporting releases the information requiring disclosure in accordance with national or international accounting and reporting standards. This information is usually released in the notes to the financial reporting, intended for a broader range of users. The notes are the most informative document, by which a user of the reporting can assess the company’s solvency, financial viability or business activity, can be informed about the terms of transactions with related parties, can make assumptions and receive data on management accounting, which are laid as the basis for the management strategy building. The released information is subject to obligatory disclosure, as its content is to be analyzed by national and international regulators and auditors in a way similar to the principal forms of financial reporting. An auditor assesses the received audit evidence in view of its sufficiency and reliability. Results of audit procedures can be summarized and documented. Because the International Standards on Auditing do not provide examples of documenting, the working document “The auditor’s testing of disclosure of the information attached to the financial reporting compiled by IFRS” has been formed, to support the process of documenting audit procedures with respect to the information given in the notes to the financial reporting. Using this working document, an auditor is able to obtain detailed information about a company and indicators of its financial reports, about its items and transactions that, not being subject to recognition in the reporting, are important for the management, about the accounting foundations and the opinions of management on which a company relied in compiling the reports. Depending on the operation specifics of a company, the working document can be supplemented by the following sections: IFRS 5 “Non-current Assets Held for Sale and Discontinued Operations”, IFRS 8 “Operational Segments”, IAS 19 “Employee Benefits”, IAS 37 “Provisions, Contingent Liabilities and Contingent Assets”, IAS 40 “Investment Property” etc. The test, which is a unified working document, can be used by any audit firm. The auditor’s opinion on the information disclosure in the notes to the financial reporting is vitally important bearing in mind that not all the users of financial reports have deep knowledge of the International Accounting and Reporting Standards, but all of them need unbiased and complete data about the company status and performance.